Inulin added electrospun composite nanofibres by electrospinning for the encapsulation of probiotics: characterisation and assessment of viability during storage and simulated gastrointestinal digestion - Duman, Dilan; Karadag, Ayse (OXFORD UNIV PRESS, 2021)
The probioticLactobacillus fermentumwas encapsulated in the electrospun nanofibres composed of polyvinyl alcohol, sodium alginate and three different inulin. The addition of inulin did not have a significant effect on electrical conductivity and surface tension of electrospinning solutions. Nanofibres showed uniform morphology with an average diameter between 200 and 400 nm. The encapsulation efficiency of probiotics was between 74.26% and 80.63%. FTIR analysis confirmed the presence of bacteria in the nanofibres. The addition of inulin improved the tensile strength and elongation at break values. Compared to free cells, encapsulated bacteria showed higher viability during the storage at 25, 4 and -18 degrees C up to 8 weeks. The survivability of cells especially encapsulated into inulin added composite nanofibres showed higher viability against simulated gastric and intestinal fluids. This study suggested that obtained composite nanofibres present a great delivery system to improve the viability of encapsulated cells against adverse conditions.
Keywords: Gastrointestinal survival; Lactobacillus fermentum; nanoencapsulation; prebiotics; FOOD; Food Science & Technology